Novel optical phenomena in graphene and photonic lattices - Liu, Fangli (2016)
In recent years, the interplay between condensed matter physics and optics has resulted into several new research branches, such as topological photonics, novel functional optical devices, realization of quantum physics in optical waveguides, etc. In this thesis, we theoretically investigate several novel optical phenomena which are related to condensed matter physics. Specifically, we focus on optical phenomena in the newly discovered two dimensional material graphene, and a tight-binding lattice model with unusual topological and localization properties. In the first part of this thesis, we demonstrate that coherent perfect absorption(CPA) of light at terahertz frequencies is achievable in graphene. We also study the plasmonic properties of novel graphene devices. This includes the non-local dispersion relation of graphene surface plasmons and a proposed device to directionally couple incident light into propagating graphene surface plasmons. In the second part of the thesis, we generalize an experimentally feasible lattice model Aubry-Andre-Harper(AAH) model by introducing a phase difference between the on-site and off-diagonal modulation strengths. It turns out that the generalized model has new localization behaviors and novel topological phenomena. The new physics of the generalized model could be experimentally observed by coupled photonic waveguides or cold atom systems. Remove selected